Different bottom trawl fisheries have a differential impact on the status of the North Sea seafloor habitats. (24th April 2020) - Rijnsdorp, A D; Hiddink, J G; van Denderen, P D; Hintzen, N T; Eigaard, O R; Valanko, S; Bastardie, F; Bolam, S G; Boulcott, P; Egekvist, J; Garcia, C; van Hoey, G; et al.
Abstract: Fisheries using bottom trawls are the most widespread source of anthropogenic physical disturbance to seafloor habitats. To mitigate such disturbances, the development of fisheries-, conservation-, and ecosystem-based management strategies requires the assessment of the impact of bottom trawling on the state of benthic biota. We explore a quantitative and mechanistic framework to assess trawling impact. Pressure and impact indicators that provide a continuous pressure–response curve are estimated at a spatial resolution of 1 × 1 min latitude and longitude (∼2 km 2 ) using three methods: L 1 estimates the proportion of the community with a life span exceeding the time interval between trawling events; L 2 estimates the decrease in median longevity in response to trawling; and population dynamic (PD) estimates the decrease in biomass in response to trawling and the recovery time. Although impact scores are correlated, PD has the best performance over a broad range of trawling intensities. Using the framework in a trawling impact assessment of ten métiers in the North Sea shows that muddy habitats are impacted the most and coarse habitats are impacted the least. Otter trawling for crustaceans has the highest impact, followed by otter trawling for demersal fish and beam trawling for flatfish and flyshooting. Beam trawling for brown shrimps, otter trawling for industrial fish, and dredging for molluscs have the lowest impact. Trawling is highly aggregated in core fishing grounds where the status of the seafloor is low but the catch per unit of effort (CPUE) per unit of impact is high, in contrast to peripheral grounds, where CPUE per unit of impact is low.